The frequency and importance of outer retinal tubulations in age related macular degeneration - Turgut, Burak; Bilir, Nagehan (My University, 2012)
Purpose: To determine the frequency of outer retinal tubulations (ORT), and to emphasize its importance in patients with age related macular degeneration (AMD). Materials and Methods: Spectral domain optical coherence tomography (OCT) scans of 405 eyes of 283 patients with AMD under follow up in our clinic were reviewed retrospectively. OCT scans were correlated with their corresponding three-dimensional retinal topographic images. The frequency, number, size, and shape of ORTs were determined and commented on. Results: The ages of the patients ranged between 60 and 85, while the mean age was 71.4±7.45 years; 101 (35.7%) were female and 182 (64.3%) were male. Two hundred forty three eyes (60%) of 405 eyes in 283 patients had atrophic AMD, and 162 (%40) had neovascular AMD. ORTs were observed in four eyes (0.99%) of four patients (1.41%), and two were refractory and neovascular AMD patients who were administered intravitreal anti-VEGF injections and developed retinal atrophy. Two patients were not administered anti-VEGF therapy and were chronic patients with atrophic AMD. While the shapes and the dimensions of ORTs showed variations, they did not respond to intravitreal anti-VEGF treatments. Conclusion: As the presence of ORT in cases of wet AMD may mean that the choroidal neovascular membrane has no exudative activity, not using these lesions as an indicator for treatment may prevent unnecessary therapeutic interventions for AMD.
Yaşa ba?li maküla dejeneresansinda diş retinal tübülasyonlarin sikli?i ve önemi
Keywords: Age-related macular degeneration; Frequency; Optical coherence tomography; Outer retinal tabulation